ASSESSMENT OF SOIL LOSS SUSCEPTIBILITY IN SANTA RITA WATERSHED IN SOUTHERN BRAZIL - Zanchin,Mayara (2021)
ABSTRACT Estimation of soil loss susceptibility is of great importance for the management of watersheds. Thus, several models for soil loss prediction have been proposed. This study estimated the total annual soil loss for the Santa Rita watershed, located in southern Brazil, using the Revised Universal Soil Loss Equation. In addition, a classification to soil loss index (ISL) was proposed to identify regions with critical soil loss values. Altitude, slope, land use, and soil class data were applied to the model, in addition to spatial information for 78 soil samples collected within the study area. It was found that there is an average annual loss of 35.94 Mg ha-1 year-1, with the most substantial loss occurring in areas with predominantly exposed soil and annual cropping. Furthermore, the ISL values indicated that approximately 50% of the study area is experiencing erosion estimates above the tolerable limit. Results emphasize the need for changes in conservation and application practices present in the watershed, considering land use and soil bearing capacity.